PENGEMBANGAN PROTOTIPE VIDEO PEMBELAJARAN SSW BIDANG PERHOTELAN SEBAGAI SALAH SATU OPSI MEDIA BELAJAR MANDIRI - Muhammad Irsan; Euis Yuniarti Yanuari (Bajang Institute, 2026)
This study was motivated by the low pass rate of candidates taking the Specified Skilled Worker (SSW) No.1 Examination in the Hospitality Accommodation field, particularly participants from Indonesia. In addition, the availability of supporting learning media remains very limited. Based on these conditions, this study aims to develop a prototype learning video as an alternative medium to support examination preparation. The research method employed was a Research and Development (R&D) approach using the ADDIE model, which consists of the stages of analysis, design, development, implementation, and evaluation. The video prototype was developed by integrating materials from the official SSW e-book, referring to the flow structure presented in reference videos, and incorporating the 5M learning approach (Observing, Questioning, Collecting Information, Associating, and Communicating), thereby promoting more interactive and contextual learning. The results of the study produced two types of video prototypes: (1) videos containing introductory material and multiple-choice practice questions along with their explanations, and (2) videos integrating visual information, such as pamphlets, as practice materials. The resulting product is expected to contribute to the development of video-based learning media in Japanese language education, particularly in the context of vocational skills training in the hospitality sector.